On the Problem of Aktionsarten in Russian - Stawnicka, Jadwiga (Respectus Philologicus, 2003)
The paper presents the classification of verbal derivatives according to Aktionsart in Russian. These derivatives represent the following Aktionsarten: temporal, Aktionsarten with a varied degree of intensity and iterative Aktionsarten. Within the scope of particular Aktionsarten, the derived verbs make groups depending on further division and formal means of expression. The article aims at the problem of explaining the various meanings of Aktionsarten.